Exploring the Influence of Digital Innovation and Paylater Features on Customer Loyalty in E-Commerce: The Mediating Role of Experiential Marketing - Slamet Heri Winarno; Lela Elvira; Bryan Givan; RR Roosita Cindrakasih (MultiTech Publisher, 2023)
The purpose of the study is to establish the manner in which experiential marketing has affected digital innovation and pay-later choices on Shoppe customers e-commerce customer loyalty. using quantitative methods and a method of non-probability sampling like simple random sampling with 100 samples. SEM (Stuctural Equation Modelling) examination of data. The research results shown that paylater's feature and characteristics related to digital innovation have a significant impact in affecting loyalty among customers, as well as how experiential marketing can be affected by paylater. However, experiential marketing fails to significantly impact consumer loyalty, and neither does digital innovation, which aims to establish customer relationships. It also has a minimal part in experiential marketing that intervenes.